The Sage encyclopedia of action research - Coghlan, David; Brydon-Miller, Mary (SAGE Reference, 2014)
This encyclopedia brings together the many strands of action research and addresses the interplay between these disciplines by presenting an overview and comprehensive breakdown of the key tenets and methods of action research as well as detailing the work of key theorists and contributors to the field.